Center of Support to Teachers and Students: evaluation for teachers and college students - Souza, Jamili Rasoul Salem de; Akerman, Marco (ABCS Health Sciences, 2015)
Introduction: Considering the various demands that are required to Higher Education, the Centre for Teaching and Student (CADD) was created to promote and expand the institutional dialogue, taking into consideration the quality of education. Objective: To evaluate the implementation of a CADD in a private Higher Education Institution (HEI) in the ABC region, throught the perception of managers, academics and students. Methods: Semi-structured interviews were conducted with participants as subjects of three groups of managers, teachers and students from guiding question. Each group met three times: before settling the CADD; in the initial phase; and one year after its implementation. Data were analyzed from a survey of selected categories that are presented in the speech of participants. Results: In its pre implementation, the subjects said they did not know CADD aims and objective; during its implementation, most respondents knew the services provided and were using them, with the active participation of teachers and administrators; and post implementation of CADD, all subjects involved already knew, approved its action and recognized the need to continue the CADD in the institution. Conclusion: This study revealed that the CADD was well received by the academic community, which reinforces its importance.